Molecular mechanisms of CYP-13 function in C. elegans: insights into conserved P450 pathways - Sharoen Yu Ming, Lim (Springer Nature, 2026)
Cytochrome P450 enzymes (CYPs) are central to metabolism and stress adaptation. In Caenorhabditis elegans, the CYP13 family performs diverse and conserved functions beyond xenobiotic detoxification. cyp-13 links lifespan regulation to the APP ortholog apl-1 and the heterochronic factor lin-14, integrating with DAF-16/FOXO, HSF-1, and DAF-12 pathways. In apoptosis, cyp-13 contributes to the degradosome complex with CPS-6/EndoG and WAH-1, facilitating DNA degradation. Several isoforms are inducible by aflatoxin B1 and PCB1254, underscoring roles in toxicant metabolism. Notably, cyp-13A12 regulates behavioral responses to reoxygenation via the EGL-9–HIF-1–PUFA–eicosanoid pathway, paralleling mammalian ischemia–reperfusion responses. Epigenetic regulation adds another layer, as BRCA1/BARD1 homologs brc-1 and brd-1 repress distinct subsets of cyp-13A genes through H2A ubiquitylation. Collectively, CYP-13 emerges as a multifunctional hub linking developmental, apoptotic, metabolic, stress, and chromatin-level processes, with clear parallels to human CYPs, highlighting its translational relevance to aging, cancer, and toxicology.